Analysis of Government Apparatus Corruption Practice in Indonesia - Setiawan, Irfan (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study is to analyze the practice of corruption in the Indonesian government and efforts to suppress corruption in the administration of government. This research was conducted with a descriptive qualitative method that discusses the phenomenon of corruption in government apparatus in Indonesia. The results of the study indicate that the practice of corruption has become an obstacle for governance by various types and levels of government administration. Greed, opportunities, needs and exposure are all factors that cause corruption. Various ways by corruptors make weak achievement of the objectives of government organizations. Corruption practices are made even more innovative, by studying gaps in the findings of financial auditors. Commitment to each element of the country is needed to improve understanding that has been formed so far. The integration of the four elements in forming an anti-corruption culture can improve understanding and anti-corruption behavior.